Two-dimensional VO2 photonic crystal selective emitter. (June 2015) - Ye, Hong; Wang, Hujun; Cai, Qilin
Abstract: The design and simulation of a two-dimensional (2D) photonic crystal (PhC) selective emitter made of vanadium dioxide (VO2 ), a type metal oxide with a high temperature resistance, are reported. Spectral emission characteristics of the 2D VO2 PhCs were investigated using the finite difference time domain (FDTD) method. The PhC consists of a periodic array of cylindrical air microcavities. The influences of the geometric characteristic parameters are discussed. The influences of the radius and depth on the emission of the 2D VO2 PhC can be explained based on the coupled-mode theory. The emissivities at wavelengths below the cut-off wavelength were enhanced by increasing the depth. When the depth was much larger than the radius, the cut-off wavelength increased with the radius. The effect of the period on the emissivity at wavelengths less than the period was highly influenced by the diffraction modes. The designed 2D VO2 PhC emitter exhibited a selective emission that was well-matched with InGaAs cells. The spectral emissivities within the convertible wavelength range of the InGaAs cells reached 0.95, and the emissivities for non-convertible wavelengths were less than 0.3. Highlights: The lattice structure of metal phase VO2 does not change with temperature. The influences of scales on the emission of a 2D VO2 PhC are discussed. A 2D VO2 photonic crystal emitter matched well with InGaAs cell is designed. The matched VO2 PhC emitter can highly improve the TPV system efficiency.